The Relationship between Nasir al-Din al-Tusi’s Moral Theory and the Normative Theories in Contemporary Moral Philosophy with an Emphasis on Virtue Ethics - Masoomeh Soleiman Meigooni; Mohammad Saeedimehr (اخلاق وحیانی)
The moral theory of Nasir al-Din al-Tusi is an important normative theory in the Islamic philosophical ethics. It is important to update this theory and specify its relationship with other normative theories in contemporary moral philosophy. Introducing the principal normative theories in contemporary moral philosophy, the present study specifies the relationship between the moral theory of Nasir al-Din al-Tusi and these contemporary ones, so that we can find the evaluation criterions for moral values in Nasir al-Din al-Tusi’s moral theory. In this way, his moral theory will be updated, which makes it possible to use this theory in applied ethics. Our findings show that Nasir al-Din’s moral theory has relationships with all three kinds of consequentialism, deontological ethics and virtue ethics. However, there are more elements of virtue ethics in his theory, so that we can say that the normative theory of Nasir al-Din al-Tusi is a version of virtue ethics. We have explained the evaluation criterions for moral values in the moral theory of Nasir al-Din al-Tusi.